PUTUSAN BEBAS (VRIJSPRAAK) DALAM KASUS KORUPSI - Sriwati Sriwati (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2018)
The allegations of corruption by was due to the indictment from the Prosecutor (Jaksa Penuntut Umum) said that the Decree that made by to move local cash (Uang Kas Daerah) from Bank J to Bank B is against the rule especially Article 4 number 5 Regulation of the Domestic Affairs (Peraturan Menteri Dalam Negeri) No. 2 Year 1994 which have been changed by Regulation of the Domestic Affairs (Peraturan Menteri Dalam Negeri) No. 2 Year 1996 stated that the local cash (uang kas daerah) should be keep on the Bank Pembangunan Daerah or other Goverment Banks (Bank Pemerintah). However, after hearing on the court it is proved that the Regulation of the Domestic Affaris (Peraturan Menteri Dalam Negeri) No.2 Year 1994 about 1mplementation of State Budget Revenue and Expenditure (Pelaksanaan APBD) which have been changed by Regulation of the Domestic Affairs (Peraturan Menteri Dalam Negeri) No. 2 Year 1996 already not applicable and had been replaced with the Government Regulation (Peraturan Pemerintah) No. 105 Year 2000 especially on the Article 33 stated that the local cash (Uang Kas Daerah) should be save by the local treasurer on the bank with a good status, and Bank B had been proved as a bank with a good status.